2008
DOI: 10.1086/525047
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Diversity of the Fecal Microbiome in RecurrentClostridium difficile–Associated Diarrhea

Abstract: Antibiotic-associated diarrhea due to Clostridium difficile (CDAD) is thought to reflect colonization of a disrupted microbial community by the pathogen. We profiled the fecal microbiota of patients with CDAD (both initial and recurrent episodes) by culture-independent phylogenetic analysis of 16S rRNA-encoding gene sequences. Compared with those from control subjects and patients with an initial episode, the fecal communities in patients with recurrent CDAD were highly variable in bacterial composition and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
654
5
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 927 publications
(712 citation statements)
references
References 14 publications
(22 reference statements)
25
654
5
16
Order By: Relevance
“…A study of the colonic microbiota in normal controls, individuals with one episode of CDI and patients with RCDI, showed that those with RCDI had a marked decrease in the diversity of the fl ora compared with the other two groups ( 84 ). Moreover, therapy that puts healthy donor stool into the stomach, small intestine, or colon of patients with RCDI (fecal microbiota transplant (FMT)) has the highest rate of success ( ≥ 90 % ) compared with results of other therapies ( 85 ).…”
Section: Management Of Rcdimentioning
confidence: 99%
“…A study of the colonic microbiota in normal controls, individuals with one episode of CDI and patients with RCDI, showed that those with RCDI had a marked decrease in the diversity of the fl ora compared with the other two groups ( 84 ). Moreover, therapy that puts healthy donor stool into the stomach, small intestine, or colon of patients with RCDI (fecal microbiota transplant (FMT)) has the highest rate of success ( ≥ 90 % ) compared with results of other therapies ( 85 ).…”
Section: Management Of Rcdimentioning
confidence: 99%
“…Recurrent CDI is thought to be the result of an inability of the intestinal microbiota to rehabilitate and re-establish itself after the initial antibiotic insult, thereby rendering the host susceptible to either a relapse with the same C. difficile strain or new re-infection with different strains of C. difficile [32,33]. In the case of the former, a major mechanism for rCDI is believed to be C. difficile spore recrudescence or persistence from the initial infection.…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 99%
“…Our knowledge of the microbial composition of the intestinal microbiota is evolving, largely due to technical advances in metagenomic analyses. Numerous studies have demonstrated decreased intestinal microbial diversity among patients with rCDI compared to those with only one episode of CDI that does not recur [33], and diversity is reduced in patients with primary or rCDI compared to those with asymptomatic colonization [33,37,38]. Other studies have shown lower proportions of the family Clostridiales Incertae Sedis XI in patients who developed CDI compared to those who did not [39][40][41].…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 99%
“…Patients with CDI harbour an intestinal microbiota with a characteristic reduced diversity owing to antibiotic use (Chang et al, 2008;Shahinas et al, 2012). We hypothesized that patients with recurrent CDI also show a composition favourable for the overgrowth of C. difficile, lacking specific signature microbes that prevent them to return to a sustainable homeostatic status after infection, resulting in recurrences.…”
Section: Introductionmentioning
confidence: 99%